Perkembangan bahasa dan sastra arab pada masa shadrul islam dan masa bani umayyah - Chasanah, Amiliyyah; Hasaniyah, Nur (Maliki Interdisciplinary Journal, 2025)
This article discusses the development of Arabic language and literature during the time of Sadrul Islam and also the Umayyad era, with a focus on changes in the political, religious and scientific context that influenced these two eras. During the time of Sadrul Islam, the Arabic language experienced development by using language as a medium for preaching. In contrast to the time of Shadrul Islam, the Umayyad era also experienced development, along with the expansion of the political power of the Umayyad dynasty. These two eras made a major contribution in forming the foundation of Arabic language and literature which is influential to this day. During the Umayyad period, Arabic reached its peak as the official language of administration and culture, supported by the development of grammar such as nahwu and balaghah. Literature during this period became complex, with themes reflecting political and social life under the Umayyad dynasty. However, the dominance of oral tradition and the weakening of religious values ​​in literary works presented a unique challenge for the development of Arabic language and literature during this period.